Rapid Rapamycin-Only Induced Osteogenic Differentiation of Blood-Derived Stem Cells and Their Adhesion to Natural and Artificial Scaffolds - Carpentieri Arianna; Cozzoli Eliana; Acri Flavio; Ranalli Marco; Diedenhofen Giacomo; Scimeca Manuel; Bonanno Elena; Gambacurta Alessandra (Hindawi Limited, 2017)
Stem cells are a centerpiece of regenerative medicine research, and the recent development of adult stem cell-based therapy systems has vigorously expanded the scope and depth of this scientific field. The regeneration of damaged and/or degraded bone tissue in orthopedic, dental, or maxillofacial surgery is one of the main areas where stem cells and their regenerative potential could be used successfully, requiring tissue engineering solutions incorporating an ideal stem cell type paired with the correct mechanical support. Our contribution to this ongoing research provides a new model of in vitro osteogenic differentiation using blood-derived stem cells (BDSCs) and rapamycin, visibly expressing typical osteogenic markers within ten days of treatment. In depth imaging studies allowed us to observe the adhesion, proliferation, and differentiation of BDSCs to both titanium and bone scaffolds. We demonstrate that BDSCs can differentiate towards the osteogenic lineage rapidly, while readily adhering to the scaffolds we exposed them to. Our results show that our model can be a valid tool to study the molecular mechanisms of osteogenesis while tailoring tissue engineering solutions to these new insights.